Celiac anti-type 2 transglutaminase antibodies induce differential effects in fibroblasts from celiac disease patients and from healthy subjects - Paolella, Gaetana; Lepretti, Marilena; Barone, Maria Vittoria; Nanayakkara, Merlin; Di Zenzo, Marina; Sblattero, Daniele; Auricchio, Salvatore; Esposito, Carla; Caputo, Ivana (Amino acids, 2017)
Type 2 transglutaminase (TG2) has an important pathogenic role in celiac disease (CD), an inflammatory intestinal disease that is caused by the ingestion of gluten-containing cereals. Indeed, TG2 deamidates specific gliadin peptides, thus enhancing their immunogenicity. Moreover, the transamidating activity seems to provoke an autoimmune response, where TG2 is the main autoantigen. Many studies have highlighted a possible pathogenetic role of anti-TG2 antibodies, because they modulate TG2 enzymatic activity and they can interact with cell-surface TG2, triggering a wide range of intracellular responses. Autoantibodies also alter the uptake of the alpha-gliadin peptide 31–43 (p31–43), responsible of the innate immune response in CD, thus partially protecting cells from p31–43 damaging effects in an intestinal cell line. Here, we investigated whether anti-TG2 antibodies protect cells from p31–43-induced damage in a CD model consisting of primary dermal fibroblasts. We found that the antibodies specifically reduced the uptake of p31–43 by fibroblasts derived from healthy subjects but not in those derived from CD patients. Analyses of TG2 expression and enzymatic activity did not reveal any significant difference between fibroblasts from healthy and celiac subjects, suggesting that other features related to TG2 may be responsible of such different behaviors, e.g., trafficking or subcellular distribution. Our findings are in line with the concept that a “celiac cellular phenotype” exists and that TG2 may contribute to this phenotype. Moreover, they suggest that the autoimmune response to TG2, which alone may damage the celiac mucosa, also fails in its protective role in celiac cells.